Pelatihan dan Pendampingan Penyusunan Business Model Canvas sebagai Strategi Penguatan Pemasaran dan Pengembangan Usaha UMKM - Septian Dwi Cahyo; Muhammad Hilmi Labibunnajah; Kuwatno Kuwatno; Eka Kurnia Patmasari; Sherli Junianingrum; Imtiyaz Farras Mufidah (Lembaga Pengembangan Kinerja Dosen, 2026)
Students as prospective entrepreneurs need the ability to design structured business models to support marketing enhancement and business development. However, many students with business ideas still lack the skills to identify target markets, formulate value propositions, and develop effective marketing strategies. This community service program aimed to improve students’ understanding and skills in developing a Business Model Canvas (BMC) as a strategy for strengthening marketing and business development. The program involved 55 students from the Faculty of Economics and Business at Universitas Selamat Sri, consisting of 44 Management students and 11 Accounting students. The methods employed included participatory training and mentoring in the preparation of the nine elements of the Business Model Canvas. The results showed that participants were able to develop more systematic business models, understand the interrelationships among business elements, identify target markets, and design marketing strategies aligned with their business ideas. Furthermore, the program enhanced entrepreneurial knowledge, awareness of business planning, and the ability to develop business ventures more effectively. Therefore, Business Model Canvas training and mentoring proved effective in strengthening students’ entrepreneurial capacity.